Introduction of Traditional Kid Game for Elementary School - Palupi, Krisna Sukmaning; , Umi Fadlillah, S.T., M.Eng (2014)
The traditional game is a game that is very fun to play but the existence of the traditional game now is already replaced by any modern game play that is not required in complex media just as the traditional game play. Play a traditional game on the computer is a good idea to keep the traditional game exist and being known by modern children. In making the application of instructional media, the author uses the method of SDLC (System Development Life Cycle) comprising the steps of : planning, analysis, design, implementation, testing and management. Besides, Construct2 is a software engine that has been chosen to make whole of this instructional media because it does not require a code to make it and can be easily converted into a mobile games, desktop games, html 5 games to play in a browser, and many more. As the animation in instructional media to be more attractive, then the object was created using the software of CorelDraw X4 and as a regulator of the sound effects is using cool edit pro version 2. The results of the study by research is forming an interesting learning media and can be played in a computer because it is been converted into a desktop application. This application consists of 10 kind of traditional games which deliver in insight and 3 kinds of games that being simulated. Based on the system testing and the retrieval of data through questionnaires to the respondents, it shows the results of the percentage of teachers 90 % and 92 % of the students say that this application is interesting.